APPRAISAL LEVEL TINGKAT PENETAPAN NJOP PAJAK BUMI DAN BANGUNAN DI KECAMATAN LOWOKWARU KOTA MALANG - Andriani, Sri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
Appraisal level determination to NJOP (Tax Object Sale Value) land and building is a measurement of the tax object sale value is used to determine besarya property tax to be paid to the government's taxpayers. While the standard used to determine in an international NJOP is the standard IAAO (International Association of Assesor Officer). Analysis of measurements with HJOP NJOP adjustment is to use ratio analysis, Coefficient of Dispersion (COD), Non-Parametric Binomial Test, Spearman Correlation, compare Mean One Sample Test. The results of the determination of the ratio analysis NJOP ground (earth) in Dinoyo has qualified for justice, while not yet eligible, In Merjosari justice, the non-parametric binomial test showed the results has been no justice from all parties and interest in the determination of both Dinoyo NJOP or in the Merjosari. Uniformity NJOP Dinoyo level determination and Merjosari Malang District Lowokwaru significantly lower, this means setting performance NJOP is not good. There is a correlation between the appraisal value with NJOP HJOP as market values. There are significant differences in the determination of both NJOP compared HJOP Dinoyo or in the Merjosari. Â Â